Computerized assessment of goal-directed behavior in Parkinson's disease. Issue 9 (20th October 2016) - Fitts, Whitney; Massimo, Lauren; Lim, Nicholas; Grossman, Murray; Dahodwala, Nabila
ABSTRACT: Introduction : Apathy is a syndrome characterized by a reduction in goal-directed behavior. Neurodegenerative diseases frequently exhibit apathy. However, we lack an objective measure of apathy. The Philadelphia Apathy Computerized Task (PACT) measures impairments in goal-directed behavior that contribute to apathy, including initiation, planning, and motivation. We sought to examine these mechanisms in Parkinson's disease (PD) patients. Method : PD patients and healthy controls with a caregiver were recruited for the study. Participants were administered the PACT, a novel computerized assessment of goal-directed behavior based on reaction times, and the Starkstein Apathy Scale (AS). Care partners completed the Neuropsychiatric Inventory (NPI). Baseline demographic characteristics of PD and control participants were compared using t tests and Wilcoxon rank sum tests. Linear regressions were used to compare PD patients to controls on each of the three PACT subtasks (initiation, planning, and motivation) while controlling for motor slowing. We then compared performance on each PACT subtask between PD subjects defined as apathetic using the NPI and Starkstein Apathy Scale and controls. Results : We included 30 PD and 15 control participants in the analysis. When controlling for motor slowing, both all PD and PD apathetic subjects were significantly slower than controls on the planning task and on the initiation task. There were no significant differences between PD patients and controls on the motivation tasks. Conclusions : PD patients showed specific initiation and planning deficits compared to control participants. After using traditional scales to define apathy, PD apathetic patients still exhibited impaired initiation and planning behaviors. These results suggest that the PACT measures aspects of impaired goal-directed behavior that may contribute to apathy in PD.